Implementation Of Accounting Information Systems In Umkm Waste Bank Assisted By Gugah Nurani Indonesia - Suti Agustin; Zulpa Okta Nita; Nova Elisabeth Hutagalung; An Suci Azzahra; Anwar Suhut (International Journal of Economic Research and Financial Accounting, 2025)
This research discusses the implementation of an Accounting Information System (AIS) at Waste Bank Berkah, which has been fostered by Gugah Nurani Indonesia since 2016. The AIS is used to support the recording of waste purchase transactions on credit, with a structured system starting from weighing, classification, to financial recording. The method used in this research is descriptive qualitative method, where data is collected through direct observation to the field, as well as collecting documentation and conducting interviews with Gugah Nurani Indonesia staff. The results of the interviews show that the AIS has a positive impact on transparency, accuracy, and customer trust, although there are still challenges such as fluctuations in waste prices and manual recording that has the potential to cause errors. To optimize financial management, it is recommended that Waste Bank Berkah start digitizing records, develop a price conversion automation feature, and strengthen training, standardization of procedures, and internal audits. Thus, the financial management of the Waste Bank is expected to be more efficient, accountable, and sustainable.